Polymeric packaging and edible coatings for minimally processed carrots - Emmambux, Mohammad Naushad (2013)
Minimally processed fruits and vegetables are increasingly demanded by local consumers and for export purposes. However, the marketing potential of these produce is limited because of physiological ageing, biochemical changes and microbiological spoilage that lead to a short shelf life. The use of polymeric packaging films to control microbial and metabolic processes and edible coatings to control the white blush formation respectively, have shown potential in improving the quality of minimally processed carrots. In combination they may form a double barrier to gases and water vapour that could provide an interaction effect to enhance the shelf life of minimally processed carrots. The aim of the study was to determine the effects of the polymeric packaging films of different permeability and edible coatings at different levels of concentration, alone and in combination on the physiological and biochemical, microbiological, and sensory quality of minimally processed carrots. A factorial experiment of 3 polymeric packaging films x 3 levels of edible coating was conducted. The three polymeric packaging films were P-Plus®, an oriented polypropylene which were fully permeable to gases and water vapour (pi, control), semi permeable (p160) and least permeable (p90) to gases only. The semi permeable and least permeable packaging had similar water vapour permeability. The coating was Nature Seal®, a cellulose based, at 0% (control), 7.5% and 15% w/w. Carrots were minimally processed into slices, dipped in the edible coating, then packed in the polymeric films and stored for 12 days at 10°C. Four packs were analysed for each combination treatment on d4, d8 and d12, and dO was taken as reference point. With time, the head space in the semi permeable packaging (p160) showed a decrease to about 11.5-13.6% oxygen and an increase to about 7.5-9.6% carbon dioxide. The least permeable pack (p90) showed an oxygen decrease to about 9.8-7.6% and a carbon dioxide increase to about 12.3-13.5%. This change showed the creation of a modified atmosphere that will decrease the metabolic activities. As the coating concentration increased, a slight increase in carbon dioxide and a slight decrease in oxygen were recorded in the head space of the packs. This change was unexpected as the coating was supposed to be a gas barrier. Thus, this change questioned the gas permeability properties of the edible coating. The polymeric packaging and the coating interacted to give lower oxygen and higher carbon dioxide levels in the head space atmosphere. However, packaging had a more pronounced effect in the creation of the modified atmospheres than the coating. A lower white blush formation and a higher retention of chroma values was recorded on the lower surfaces of the carrot slices than on the upper surfaces (upper surfaces refer to those that were facing the packaging material, the lower surfaces was the opposite side of the upper surfaces). This showed that the relative humidity gradient was probably not the same between the surfaces. The coating effectively controlled the white discolouration and maintained higher chroma values on both surfaces of the carrot discs, but packaging did not affect the colour changes of the upper surfaces. An interaction effect was also observed between the packaging and coating showing a better control of the white blush formation of the lower surfaces of the carrot discs. Yeast and moulds did not prove to be a problem in minimally processed carrots as they were lower than 103 cfu/g carrots throughout the storage period. When the carrots were visibly spoiled, the lactic acid bacteria were over 106 cfu/g and the psychrotrophs were about 107 to 108 cfu/g. Initially, a high growth rate of psychrotrophic bacteria occurred followed by a high growth rate of the lactic acid bacteria. This showed a dynamic relationship between the two microbes. Visible rot was observed by brown discolouration, tissue softening and exudate production. The packaging controlled the microbiological growth and spoilage as compared with the coating that enhanced it. A decrease in pH from d4 to d12 corresponded to an increase in the lactic acid bacteria and visible spoilage. Combination of edible coatings and polymeric packaging films did not show any synergistic or additive effects to enhance the shelf life of minimally processed carrots despite some interactions between these two variables. This was because the polymeric packaging films primarily prevented microbiological growth and spoilage, whereas edible coatings partly controlled white blush formation. White blush formation was the most important shelf life determinant of minimally processed carrots. Research efforts should therefore be focused on overcoming this defect. === Dissertation (MSc (Food Science))--University of Pretoria, 2007. === Food Science === unrestricted